2017
DOI: 10.1080/2000656x.2016.1269776
|View full text |Cite
|
Sign up to set email alerts
|

Scandcleft randomised trials of primary surgery for unilateral cleft lip and palate: 3. Descriptive study of postoperative nursing care following first stage cleft closure

Abstract: ISRCTN29932826.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…In the literature, a study reported the high dependency unit admission rate as 2.7%, and the mean length of stay in ICU was 12.9 to 24.98 hours. 14 However, in this study, further data such as etiology of ICU/high dependency unit admission, the type of the admission (expected/unexpected), the association of the cleft type with admission, treatment/follow-up protocol in the ICU have not been examined. The higher rate of ICU admission and the long stay in the ICU of the present study is attributed to admissions and consultations of the challenging patients to our clinic, as our hospital is a tertiary healthcare center and is the referral hospital for CLP management with a comprehensive cleft team.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In the literature, a study reported the high dependency unit admission rate as 2.7%, and the mean length of stay in ICU was 12.9 to 24.98 hours. 14 However, in this study, further data such as etiology of ICU/high dependency unit admission, the type of the admission (expected/unexpected), the association of the cleft type with admission, treatment/follow-up protocol in the ICU have not been examined. The higher rate of ICU admission and the long stay in the ICU of the present study is attributed to admissions and consultations of the challenging patients to our clinic, as our hospital is a tertiary healthcare center and is the referral hospital for CLP management with a comprehensive cleft team.…”
Section: Discussionmentioning
confidence: 97%
“…In a study reporting the ICU admission rate, different repair techniques of different centers have been compared. 14 However, this study has not analyzed the etiology of the ICU admission, such as associated syndromes and concomitant anomalies. Furthermore, to our knowledge, there is not presented ICU admission rate and associated data of CLP patients without additional medical issues in the literature.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Cleft lip and palate is one of the most common congenital anomalies requiring surgical treatment in children, normally commenced in the first year of life [6]. Routine laboratory testing has minimal impact on management and outcome of orofacial cleft surgeries.…”
Section: Background Of the Studymentioning
confidence: 99%